Analytical Study: the Use of Digital Technology-Based Learning Media at Alam Surya Mentari Elementary School - Alviana Metasari; Nur Amalia (Elementary Teacher Education Program, Majalengka University, 2024)
This research is motivated by examining the use of digital technology-based learning media at Alam Surya Mentari Elementary School, where the existence of digital technology-based learning media is important for teachers to use in the current 4.0 era. Digital technology-based learning media is a means of supporting learning activities using digital media as a tool used by teachers in providing effective, creative and efficient learning activities to students according to the learning that will be discussed. Therefore, this research aims to analyze the use of digital technology-based learning media that teachers have used during learning activities with students at SD Alam Surya Mentari, because basically the school is a natural school that adheres to a direct learning system with nature. This research uses qualitative research methods, with a case study design. The data that has been collected in this research was carried out using interview data, observation and documentation. The analysis technique uses three stages, namely data reduction, data presentation and drawing conclusions. The results of this research show that teachers at SD Alam Surya Mentari have carried out teaching and learning activities using digital technology-based learning media as a tool if learning material media for students cannot be obtained directly around the school. So from this research it is concluded that learning media with a learning system with nature remains the main media for Alam Surya Mentari Elementary School teachers, while learning media based on digital technology is only used to support visual material.